Electrospun silk fibroin‐based neural scaffold for bridging a long sciatic nerve gap in dogs. (2nd August 2017) - Xue, Chengbin; Zhu, Hui; Tan, Dehua; Ren, Hechun; Gu, Xiaokun; Zhao, Yahong; Zhang, Ping; Sun, Zhichao; Yang, Yumin; Gu, Jianhui; Gu, Yun; Gu, Xiaosong
Abstract: Silk fibroin (SF)‐derived silkworms represent a type of highly biocompatible biomaterial for tissue engineering. We have previously investigated biocompatibility of SF with neural cells isolated from the central nervous system or peripheral nerve system in vitro, and also developed a SF‐based nerve graft conduit or tissue‐engineered nerve grafts by introducing bone marrow mesenchymal stem cells, as support cells, into SF‐based scaffold and evaluated the outcomes of peripheral nerve repair in a rat model. As an extension of the previous study, the electrospun technique was performed here to fabricate SF‐based neural scaffold inserted with silk fibres for bridging a 30‐mm‐long sciatic nerve gap in dogs. Assessments including functional, histological and morphometrical analyses were applied 12 months after surgery. All the results indicated that the SF‐based neural scaffold group achieved satisfactory regenerative outcomes, which were close to those achieved by autologous nerve grafts as the golden‐standard for peripheral nerve repair. Overall, our results raise a potential possibility for the translation of SF‐based electrospun neural scaffolds as an alternative to nerve autografts into the clinic.